2021
DOI: 10.3390/ijerph18041474
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction during Forced Social Distancing and Home Confinement Derived from the COVID-19 Pandemic in Spain

Abstract: Life satisfaction is one of the main dimensions of well-being related to psychological factors, being essential for a person to adjust to difficult circumstances. The restrictive measures adopted to minimize the diffusion of the coronavirus disease (COVID-19) could alter the subjective dimension of well-being, so the objective of this study was to determine the factors related to life satisfaction of the Spanish population during forced home confinement derived from the COVID-19 pandemic. A cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 57 publications
(79 reference statements)
3
33
0
Order By: Relevance
“…In our study, women suffered higher levels of psychological distress (i.e., symptoms of anxiety and depression) and made more consultations to improve their mood, a finding that is mirrored in various other studies [ 6 , 7 , 19 , 20 , 28 , 46 , 48 ]. Additionally, they were less optimistic about the future, both on a personal level and with regard to society in general.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, women suffered higher levels of psychological distress (i.e., symptoms of anxiety and depression) and made more consultations to improve their mood, a finding that is mirrored in various other studies [ 6 , 7 , 19 , 20 , 28 , 46 , 48 ]. Additionally, they were less optimistic about the future, both on a personal level and with regard to society in general.…”
Section: Discussionsupporting
confidence: 83%
“…During the first week of lockdown, high levels of life satisfaction and perceived good health were cut nearly in half, and they gradually decreased over the following weeks. Many authors have focused their efforts on studying the impact of COVID-19 on levels of life satisfaction during lockdown, in addition to other possibly related factors [ 46 , 47 ]. In our study, though we address this aspect with a single overall question, the results obtained coincide with those from the aforementioned studies that use multidimensional scales.…”
Section: Discussionmentioning
confidence: 99%
“…Research performed in Saudi Arabia found a 55.5% prevalence of high levels of stress during the quarantine, which was reduced by cognitive reappraisal and life satisfaction [68]. Numerous studies showed that the primary source of stress during the coronavirus pandemic was the significant lifestyle changes, related in particular to numerous restrictions and social isolation [17,[38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from 30 May 2020, wearing masks in outdoor places was no longer obligatory but was restored as of 10 October 2020 due to the increasing number of cases. Primary lockdown-related stress sources were as follows: isolation, restriction in moving, shopping, traveling, changes in daily lifestyle regards use of face masks, washing hands frequently, avoiding social contact and gatherings, restaurants, pubs, clubs, fitness clubs, limiting physical activity outdoors, and required remote online learning and work [17,[38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is a profession with distinct dimensions that bring joy and satisfaction, but it also involves many difficulties and dilemmas (Bartosiewicz et al, 2020 ). High life satisfaction is associated with better physical and mental health, and life satisfaction is important in terms of adapting to adversity (Gonzalez-Bernal et al, 2021 ). In the literature, we found one study on life satisfaction during the COVID-19 pandemic that included nurses in the sample group (Teke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%